HUMAN CAPITAL MANAGEMENT AND THE GROWTH OF SMALL AND MEDIUM SCALE ENTERPRISES IN EMENE, ENUGU STATE - ESTHER, DR.; MADUAGWU, NNEKA; EDWIN M, DAPPER; ERIC I, NLEMEDIM (IJRDO - Journal of Business Management, 2017)
his study focused on Human Capital Management and the Growth of Small and Medium Scale Enterprises Emene, Enugu State. This study adopted a descriptive survey approach and it covered a population of 84 personnel drawn from 5 SMEs. Yaro yamene was used to select a sample of 69 respondents from the population. Data used in the study was gathered using a five point likert scale questionnaire and was analyzed using the one sample kolmogorov Smirnov statistic (K-S). The K-S value from the SPSS output for hypothesis one is 0.798 while it is 0.458 for hypothesis two. The study conclude that most SMEs do not give adequate attention to staff training and this reduces the capability of their employees to deliver on the task for which they are hired. It was therefore recommended that SMEs must as a matter of strategic urgency, rethink their human capital management practices especially in the area of the provision of staff industry-specific skill development programmes and the offering of reward and compensation packages that are competitive if they must attract and retain quality workforce which is a sine-quanon for sustainable growth.